An Intellectual Exploration of Betawi Ulama’s Da‘wah Thought in Colonial Batavia: A Systematic Review from the Perspective of Islamic Intellectual History - Mohamad Sutan Khadafi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
Research on Islamic intellectual history has undergone significant development over the last two decades, particularly through efforts to decolonize knowledge and critique narratives of the “decline” of Islamic civilization. Addressing this scholarly shift, this study conducts a systematic review of the da‘wah thought of Betawi ulama in colonial Batavia within the framework of Islamic intellectual history. Using a systematic review method that synthesizes primary and secondary historiographical sources, this study identifies five major thematic orientations: da‘wah as moral and social education; da‘wah as cultural resistance to colonialism; religious moderation in da‘wah practices; the production of textual works as da‘wah instruments; and the articulation of Betawi Islamic identity. The findings reveal that Betawi ulama’s da‘wah was not limited to religious instruction but also functioned as a medium for preserving cultural religious identity and articulating subtle forms of resistance against Dutch colonial power. This study contributes to the broader discourse on Islamic intellectual history by highlighting the role of local scholars in shaping social solidarity and advancing the decolonization of Islamic knowledge in Indonesia. The novelty of this research lies in its systematic synthesis of Betawi ulama’s intellectual contributions an area that remains understudied in both Indonesian historiography and global Islamic intellectual studies.